2019
DOI: 10.1111/jnc.14721
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alpha‐synuclein post‐translational modifications on metal binding

Abstract: Parkinson’s disease is the second most common neurodegenerative disorder worldwide. Neurodegeneration in this pathology is characterized by the loss of dopaminergic neurons in the substantia nigra, coupled with cytoplasmic inclusions known as Lewy bodies containing α‐synuclein. The brain is an organ that concentrates metal ions, and there is emerging evidence that a break‐down in metal homeostasis may be a critical factor in a variety of neurodegenerative diseases. α‐synuclein has emerged as an important metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 160 publications
2
59
0
Order By: Relevance
“…Metal dyshomeostasis has long been linked to PD [18][19][20], and victims of PD present with increased cerebral iron levels and diminished levels of copper in affected regions of the brain. Although the precise roles of brain metals on the function of NAc αSyn have yet to be elucidated, we [10,[21][22][23] and others [9,24,25] have demonstrated how prevalent brain biometals modulate the structural outcome of NAc αSyn self-assembly pathways and influence both the potential and the extent of its aggregation.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Metal dyshomeostasis has long been linked to PD [18][19][20], and victims of PD present with increased cerebral iron levels and diminished levels of copper in affected regions of the brain. Although the precise roles of brain metals on the function of NAc αSyn have yet to be elucidated, we [10,[21][22][23] and others [9,24,25] have demonstrated how prevalent brain biometals modulate the structural outcome of NAc αSyn self-assembly pathways and influence both the potential and the extent of its aggregation.…”
Section: Introductionmentioning
confidence: 87%
“…Fe II supplementation resulted in a moderate decrease in the overall fluorescence emission of dityrosine crosslinks within NAc WT, while Fe III supplementation enhanced overall dityrosine crosslinking in NAc WT. Iron is thought to bind within the C-terminal region of NAc αSyn [9,18,24], within close proximity to the three C-terminal tyrosine residues. Previously, we reported that Fe blocks Cu-induced photoinitiated dityrosine crosslinking in NAc αSyn [23], and our current results further suggest that Fe II also results in a relative decrease in dityrosine crosslinking compared to the unmetalated native protein.…”
Section: Photoinduced Dityrosine Formation Of Fe-bound Nac αSyn Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments utilizing ESI-MS (electrospray ionization mass spectrometry) technology revealed several modifications of α-synuclein in PD brains, such as N-or C-terminal truncations and phosphorylation at Ser129 (Kellie et al, 2014). In healthy brain, only a small proportion of α-synuclein is phosphorylated (Gonzalez et al, 2019), whereas under pathological conditions phosphorylated α-synuclein -mostly at Ser129-is increased in the majority of pathological inclusions, including LBs in PD and DLB, GCIs in MSA and LB-type inclusions of AD (Fujiwara et al, 2002;Saito et al, 2003;Nishie et al, 2004;Waxman et al, 2009). Even though initially phosphorylation of α-synuclein was considered to act prophylactically to protein aggregation, it is now widely accepted that it precedes fibril formation (Shahpasandzadeh et al, 2014;Tenreiro et al, 2014;Oueslati, 2016).…”
Section: The Structure Function and Aggregation Of α-Synucleinmentioning
confidence: 99%
“…The issue will also focus on molecular aspects of aSyn. González and colleagues review the understanding of the role of PTMs and metals on the aggregation and toxicity of aSyn (González et al ). Alam and colleagues expand this concept and provide their views on the process of aSyn aggregation and the possible occurrence of strains, which could explain different spreading patterns, and constitute the molecular underpinnings for different synucleinopathies (Alam et al ).…”
mentioning
confidence: 99%